2022
DOI: 10.3390/microorganisms10071390
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparison of Ocular Surface Microbiome in Newborns

Abstract: The ocular microbiome is of fundamental importance for immune eye homeostasis, and its alteration would lead to an impairment of ocular functionality. Little evidence is reported on the composition of the ocular microbiota of term infants and on the impact of antibiotic prophylaxis. Methods: A total of 20 conjunctival swabs were collected from newborns at birth and after antibiotic treatment. Samples were subjected to 16S rRNA sequencing via system MiSeq Illumina. The data were processed with the MicrobAT soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…As can be observed, most of the patients had limited heterogeneity, indicating low biodiversity. The biodiversity was assessed using an index, defined by the MicrobAT ® software (Microbiota Analysis Tool; SmartSeq S.r.l., Italy) [ 22 , 23 ]. Biodiversity is defined by the number of spp populations observed and is an indicator of the health of the microbiota—the lower the result is, the lower the number of microbial populations detected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be observed, most of the patients had limited heterogeneity, indicating low biodiversity. The biodiversity was assessed using an index, defined by the MicrobAT ® software (Microbiota Analysis Tool; SmartSeq S.r.l., Italy) [ 22 , 23 ]. Biodiversity is defined by the number of spp populations observed and is an indicator of the health of the microbiota—the lower the result is, the lower the number of microbial populations detected.…”
Section: Resultsmentioning
confidence: 99%
“…Raw sequencing data were uploaded to a bioinformatic system. Taxonomic assignment and a bioinformatic analysis were performed using the MicrobAT ® software (Microbiota Analysis Tool; SmartSeq S.r.l., Novara, Italy) [ 22 , 23 ]. In the first phase of the analysis, reads were cleaned by a dedicated algorithm to remove short, low-quality sequences.…”
Section: Methodsmentioning
confidence: 99%
“…With chloramphenicol, although resistance among ocular isolates is generally low, a few studies have reported high rates of resistance [9]. Topical antimicrobial exposure may also disrupt the paediatric microbiome at the ocular surface [10], and an altered microbiome has been reported in some ocular surface disorders [11]. With chloramphenicol, although there is no strong evidence linking topical use with haematotoxicity, topical chloramphenicol is not in use in the United States, due to concerns around this rare adverse effect being linked to systemic administration [12].…”
Section: Introductionmentioning
confidence: 99%
“…Viruses are the leading cause of infectious conjunctivitis, followed by bacteria, although fungi and parasites may be involved in the progress of infection [ 12 ]. The microorganisms that cause conjunctivitis can be acquired by direct contact with hands and objects contaminated by the etiological agent, aerosol transmission, and vertically from mother to child [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%